Precarity in the Brussels-Capital Region: The Issues at Stake for Public Policy in Response to the Precarization of Single-parent Families in Brussels - Martin Wagener (Oñati Socio-Legal Series)
The process of precarization is analysed in different manners in most literature concerning contemporary stakes of western welfare states. In comparison to other countries, Belgium has known a rather specific and delimited effect of the economic crisis from 2008, but certain groups face rather an ongoing effect of precarization on multiple and intertwined aspects. The aim of the article is to analyse the situation of precarity of single-parent families in the Brussels-Capital Region. The attention to that group is related to its higher risk of precarity and poverty. Furthermore it allows analysing the limits of public policies in the fight against poverty and precarity, that are clearly inadequate.